A CHALLENGING CASE OF GRAVES’ DISEASE WITH MYELODYSPLASTIC SYNDROME - Menon, Saieehwaran; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Graves’ disease is an autoimmune condition where antibodies are produced against the thyrotropin (TSH) receptors on the thyroid gland. The condition can be associated with haematologic manifestations. CASE A 44-year-old male with underlying Graves’ disease, Schizophrenia, Chronic Hepatitis B and Myelodysplastic Syndrome presented with a week’s history of loose stools and vomiting. On examination, blood pressure was 115/78 mmHg and heart rate was 97 bpm. He had pallor, tremors, sweaty palms, and a small goitre. Thyroid function tests were: TSH <0.001 m IU/L (0.27-4.2), T4 21.9 pmol/L (12.0-22.0), T3 2.65 pmol/L (3.1-6.8). His complete blood count was: Hb 11.7 g/dl (13-17), WBC 3.52 x 109 /L (4-10), ANC 1.68 x 109 /L (2.0-7.0), Platelets 69 x 109 /L (150-410). He was started on a thionamide with close monitoring of blood counts. However, the thionamide was withheld in view of his reducing absolute neutrophil count. He was then treated with steroids, lithium and cholestyramine with no improvement in his thyroid function tests. Hence, he was eventually given radioactive iodine. Graves’ disease with myelodysplastic syndrome proves to be challenging for endocrinologists to treat. The probable underlying pathophysiology is that high blood levels of thyroid hormones can be toxic to bone marrow cells leading to an increase in functional activity of reticuloendothelial cells, causing insufficient hematopoietic cells. In one study, free T3 and T4 were noted to be higher with lower TSH in patients with myelodysplastic syndrome. In view of the difficulty of treating hyperthyroidism with anti-thyroid drugs, our patient was treated with radioiodine ablation. CONCLUSION In conclusion, managing Graves’ disease in individuals with myelodysplastic syndrome requires detailed evaluation and monitoring.